The Integration of Science and Technology in Islamic Fiqh: A Contemporary Perspective - Betti Feriati; Rini Nopita; Haris Riadi; Harmaini Harmaini; Siti Sulwana; Fatimah Uri (Indonesian Journal of Education Research (IJoER), 2025)
Purpose of the study: This study aims to explore how fiqh provides moral and ethical foundations for integrating science and technology within the framework of maqāṣid al-sharī‘ah. Methodology: This research employs a qualitative descriptive-analytical method using a literature review approach. Primary data sources include classical and contemporary fiqh texts, supported by scholarly works on the integration of science and technology. The study also examines qiyās and ijtihād as dynamic tools for addressing contemporary scientific and technological challenges. Main Findings: The findings reveal that fiqh offers a structured ethical framework to align scientific and technological advancements with sharī‘ah principles. Through maqāṣid al-sharī‘ah, it ensures that technological progress remains within moral and spiritual boundaries, promoting accountability and ethical responsibility. The study highlights how ijtihād plays a crucial role in interpreting new developments in light of Islamic jurisprudence. Novelty/Originality of this study: This study provides a fresh perspective by linking fiqh principles with contemporary scientific and technological challenges. It contributes to the ethical governance of scientific advancements while reaffirming the relevance of fiqh in addressing modern issues through qiyās and ijtihād.